Brief and further details regarding the harmful lawful acts in the Peruvian legal system: analysis of some specific cases - Campos García, Héctor Augusto (2016)
This article addresses the issue referred to harmful lawful acts which also generate liability, thus ruling out the unlawfulness as an essential element for the generation of liability. In this regard, the author makes a conceptual analysis of the unlawfulness or illegality, and he examines three cases of liability, such as environmental damage, the interim resolution and withdraw the work of trade; demonstrating, effectively, the dispensable nature of the unlawfulness and the existence of scenarios of liability arising from harmful lawful acts.